2012
DOI: 10.1021/la2047504
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Responsive Reversible Molecule-Gated System Using Thymine-Modified Mesoporous Silica Nanoparticles

Abstract: In this paper, a reversible light-responsive molecule-gated system based on mesoporous silica nanoparticles (MSN) functionalized with thymine derivatives is designed and demonstrated. The closing/opening protocol and release of the entrapped guest molecules is related by a photodimerization−cleavage cycle of thymine upon different irradiation. In the system, thymine derivatives with hydrophilicity and biocompatibility were grafted on the pore outlets of MSN. The irradiation with 365 nm wavelength UV light to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 38 publications
0
60
0
Order By: Relevance
“…described a light-operated system in which thymine derivatives were grafted on the pore outlet of MSNs (Type II) [51]. When the thymine-modified MSNs were exposed to 365 nm UV light irradiation, cyclobutane dimmers formed in the pore entrances, which blocked the pores.…”
Section: Msn-based Sustained Drug Delivery Systemsmentioning
confidence: 99%
“…described a light-operated system in which thymine derivatives were grafted on the pore outlet of MSNs (Type II) [51]. When the thymine-modified MSNs were exposed to 365 nm UV light irradiation, cyclobutane dimmers formed in the pore entrances, which blocked the pores.…”
Section: Msn-based Sustained Drug Delivery Systemsmentioning
confidence: 99%
“…[647] In this case, therapeutic cargos are capable of releasing their payloads due to the presence of organic or inorganic moieties [640] www.advancedsciencenews.com www.advhealthmat.de that are responsive to a certain stimuli. [648] Special gate keepers such as coumarin molecules, [649] azobenzene molecules, [650] thymine, [651] and polymers [652] which are responsive to light source as well as grafting of thermosensitive polymers based on poly-N-isopropylacrylamide (PNIPAM) and its derivatives [652,653] have been exploited for a very precise control release of therapeutics in mesoporous silica coated nanoparticles. In a very recent study, Saint-Cricq et al [652] reported design of thermoresponsive polymeric cap for magnetic core-shell Fe 3 O 4 @ SiO 2 mesoporous nanoparticles by incorporating azo bonds into the backbone of poly(ethylene glycol) (azo-PEG) for a controlled drug release (Figure 40).…”
Section: Magnetic Drug Targetingmentioning
confidence: 99%
“…In recent years, mesoporous silica nanomaterials have attracted much attention as drug delivery carriers due to their unique advantages, such as high specific surface area and large pore volume, homogeneous controllable particle size, easily modified surface and good biocompatibility Zhang et al, 2010Zhang et al, , 2014Mellaerts et al, 2008). Moreover, mesoporous silicaassisted drug delivery systems have increasingly focused on stimuli-responsive CDDSs that can release encapsulated drugs from silica carriers at the expected site in response to various stimuli including pH, redox potential, temperature, photoirradiation, and biomacromolecule (Yang et al, 2012;Meng et al, 2010;Zhou et al, 2007;He et al, 2012;Bernardos et al, 2010). Many available functionalized mesoporous silica nanoparticles (MSNs) have been developed to regulate drug release by capping the outlets of mesopore or encapsulating drugs within the porous channels of MSNs.…”
Section: Introductionmentioning
confidence: 99%